2007
DOI: 10.1002/app.25572
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, mechanical, and morphological studies of epoxy/poly(methyl methacrylate) semi‐interpenetrating polymer networks

Abstract: Semi-interpenetrating polymer networks (semiIPNs) of epoxy resin and poly(methyl methacrylate) (PMMA) were synthesized. Methyl methacrylate (MMA) was polymerized by free radical mechanism with azo-bis-isobutyronitrile in the presence of oligomeric epoxy resin (DGEBA), and hexahydrophthalic anhydride as crosslinking agent. The gelation and vitrification transitions during cure/polymerization processes have been examined using parallel-plates rheological technique. From differential scanning calorimetry and rheo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…43 The vitrification time (t vitr ) has been determined as the time corresponding to the maximum G̕ ̕ peak. 44,45 The obtained gel time and vitrification time for the epoxy, epoxy/ clay nanocomposites and epoxy/clay/CTBN hybrid at different curing temperatures are tabulated in Table 2. It was observed that epoxy/3 phr I.28E mixture attained the gelation and vitrification in a shorter time compared to neat epoxy, while epoxy/3 phr I.30E system has a delayed gelation and vitrification than that of the neat epoxy.…”
Section: Resultsmentioning
confidence: 99%
“…43 The vitrification time (t vitr ) has been determined as the time corresponding to the maximum G̕ ̕ peak. 44,45 The obtained gel time and vitrification time for the epoxy, epoxy/ clay nanocomposites and epoxy/clay/CTBN hybrid at different curing temperatures are tabulated in Table 2. It was observed that epoxy/3 phr I.28E mixture attained the gelation and vitrification in a shorter time compared to neat epoxy, while epoxy/3 phr I.30E system has a delayed gelation and vitrification than that of the neat epoxy.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the combination of these general classes of polymers being investigated previously, research has generally been concerned with a combination of two rigid, high T g polymers [30]. In this case, by using a combination of high and low T g polymers the opportunity exists to not only tailor the morphology of these two distinct systems, but to manipulate the mechanical properties over a wide range.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the gel time is dependent on both the curing temperature and the MWCNT content. That is, the gel time decreases as the cure temperature increases, resulting in the cure reaction occurring more rapidly [11]. This is probably due to the increase of molecular mobility.…”
Section: Rheological Propertiesmentioning
confidence: 97%